Analysis of the Development Level of Rural-Border Areas in Belu and Malaka Regencies - Hidayah, Ulul; Farisa Maulinam Amo; Anggelina Delviana Klau; Sandra Andrea Giri (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Border areas became a development priority in the Nawacita era, so many programs were carried out to support the acceleration of development in these areas. Belu and Malaka regencies are one of the border areas in the Indonesia Republic that borders the Democratic Republic of Timor Leste (RDTL). The aim is to see changes in the level of development of rural borders in the Belu and Malaka Regencies. The data used in this research is the Rural Development Index (IDM). The data that has been collected is then carried out with descriptive statistical analysis using a spatial approach. The results of this research explain that the level of development of rural borders in Belu Regency has experienced positive changes. However, rural borders in Malaka Regency have yet to undergo significant changes in the level of village development. It is because of the differences in the two regions' initial years of border development interventions. Belu Regency has priority in border area development compared to Malaka Regency. Belu Regency has a special program and budget from presidential instructions to accelerate border development. The case studies of the two districts suggest that the government should allocate a special budget to support policy implementation.